Kinship diplomacy between Sicily and Rome - Prag, J (Salvatore Sciascia editore, 2011)
"The phenomenon of kinship diplomacy, if not perfectly defined, is nonetheless widely understood and extensively studied. The presence of kinship diplomacy in the political interactions between Rome and other Mediterranean states has in turn received specific treatment. At the same time, the extent of kinship claims in the island of Sicily and the associated claims about origines made by many of the communities on the island have also been studied in very considerable detail. In other words, this paper does not intend to cover new ground – indeed, the individual case studies upon which I shall focus have themselves been the objects of considerable attention. However, it is fair to state that the several instances of kinship diplomacy which can be documented between Sicilian communities and Rome have so far not been considered as an ensemble (although individually often considered in relation to one or more of the other instances). In itself, that would not necessarily be sufficient reason to justify a fresh study. The further argument that the Sicilian cases deserve to be better known, not least because they present a number of unusual features, could likewise be dismissed as special pleading. A more serious argument however remains, and this is that consideration of the Sicilian cases in their own right, and as a group, strongly suggests a more diverse and earlier use of the phenomenon of kinship diplomacy, in relation to Rome, than is commonly accepted." (From the Introduction)